A Lost Generation? Impact of COVID-19 on High School Students' Achievements - Dalit Contini; Maria Laura Di Tommaso; Caterina Muratori; Daniela Piazzalunga; Lucia Schiavon (Institute of Labor Economics (IZA), 2023)
This paper estimates the effect of a full year of the COVID-19 pandemic on school performance, focusing on students at the end of upper secondary school who are about to enter the labour market or start university without having had the opportunity to recover. Using longitudinal data from standardised tests for the student population nationwide, we use difference-in-differences models to analyse the performance of two cohorts of students in Italy: a cohort that has never been exposed to the pandemic and a cohort that graduated in 2021. We find that the pandemic had a huge negative impact on students' performance in mathematics and reading (approximately 0.4 s.d. in both domains). Low-achieving pupils suffered the most, increasing the gap between strong and poor performers. The relative position of girls improved compared to boys. Different from the findings from the existing literature, inequalities by parental education remained largely unchanged.
Keywords: I21; I24; I18; I28; 330; COVID-19; school closure; learning loss; standardised tests; inequality